Effect of paclobutrazol on plant growth, yield and fruit quality in tomato - Ramos-Fernández, Josúe; Ayala-Garay, Oscar J.; Pérez-Grajales, Mario; Sánchez-del Castillo, Felipe; Magdaleno-Villar, J. Jesús (Bioagro, 2020)
There are few studies on the effect of the growth retardant Paclobutrazol (PBZ) on the entire tomato production cycle. In this research, vegetative and reproductive variables of the plant were studied in the indeterminate hybrid El Cid under greenhouse. Five treatments were evaluated from zero to four applications (25, 77, 92 and 107 days after sowing), with doses of 50 mg∙L-1, in a completely randomized design with four repetitions using ten plants as the experimental unit. The PBZ (Cultar 25 SC) was applied to the foliage. Plant height and length of the internodes were reduced in relation to the untreated plants, and the effect was greater as the number of applications increased. The number of internodes was not affected. The fruit yield increased (P≤0.05) when the plants received four applications, presenting approximately 30 fruits with 3,573 kg of total weight per plant, and in the untreated 26 fruits and 3,078 kg per plant. Average fruit weight, pericarp thickness, and soluble solids content were similar in treated and untreated plants. With applications up to the fifth flowering, a total of four applications were the most efficient in reducing plant height and improving yield per plant, without affecting the quality of the fruit.